The Effect Of Capital Structure And Intellectual Capital On Economic Value Added With Profitability As An Intervening Variable In The Primary Consumer Goods Sector Listed On The Indonesia Stock Exchange - Reza Ajeng Rahayu; Sutisna Sutisna; Gema Ika Sari (Amkop Management Accounting Review (AMAR), 2026)
In the business world, creating value and wealth for shareholders is the primary goal. Traditional financial statements are often criticized for not fully accounting for the total cost of capital, including the cost of equity capital, which led to the emergence of modern performance measures like Economic Value Added (EVA) that are considered more comprehensive. However, research shows the volatility of EVA values in primary consumer goods sector companies on the Indonesia Stock Exchange (IDX) during the 2019-2020 and 2022-2024 periods, which even showed a negative figure in 2024. This indicates a decrease in company value and an inability to create additional economic value above the cost of capital. This issue highlights the importance of researching the factors that influence it, such as capital structure and intellectual capital. This study aims to analyze the effect of capital structure and intellectual capital on Economic Value Added (EVA), with profitability (Return on Equity) as an intervening variable, in primary consumer goods sector companies listed on the IDX during the 2019-2020 and 2022-2024 periods. This quantitative research uses secondary data from financial statements and applies the panel data regression analysis method to test the relationship between variables. The results of this study are expected to provide a comprehensive understanding for company management and stakeholders on how efficient financial strategies and intellectual capital management can contribute to the creation of economic value added.